PEER ASSISTED LEARNING (PAL) PROGRAM AT SKILLS-LAB, WAINGAPU NURSING STUDY PROGRAM, HEALTH POLYTECHNIC, KUPANG - Landi, Melkisedek; Prabandari, Yayi Suryo; Tridjoko Hadianto; Umbu Nggiku Njakatara; Umbu Putal Abselian (Poltekkes Kemenkes Kupang, 2025)
Background: Many studies have reported efficacy of the PAL, but the application has not been a lot of diploma programs. Purpose: To determine differences between PAL tutor guidance and skills lab perception. Method: Quantitative studies, randomized control trial the first year nursing diploma students (N=94). PAL tutor students second year, 5 experimental groups and 5 control group, for both of skills PAL tutor guidance and skills lab perception within 2 weeks. Results: Mean first intervention group 83.15 and the control group 78.91 Mean second intervention group 91.24 and the control group 79.79. Mann-Whitney first intervention 0.238 and second 0.001. Mean perception PAL 4.45 to 4.67 of the range 5. Spearman Correlation first perception 0.173. and perception of both -0.265. Conclusions and Recommendations: Students who attend PAL value higher than that do not follow PAL. Student perceptions about the PAL is good. Further research needs to be done PAL relationships between learning styles, GPA, good motivation for PAL tutors and participants.